Saturating effects of species diversity on life-history evolution in bacteria - Barraclough,TG; Bell,T; Scheuerl,T (Proceedings of the Royal Society of London. Series B, Biological Sciences, 2015)
Species interactions can play a major role in shaping evolution in new environments. In theory, species interactions can either stimulate evolution by promoting coevolution or inhibit evolution by constraining ecological opportunity. The relative strength of these effects should vary as species richness increases, and yet there has been little evidence for evolution of component species in communities. We evolved bacterial microcosms containing between 1 and 12 species in three different environments. Growth rates and yields of isolates that evolved in communities were lower than those that evolved in monocultures, consistent with recent theory that competition constrains species to specialize on narrower sets of resources. This effect saturated or reversed at higher levels of richness, consistent with theory that directional effects of species interactions should weaken in more diverse communities. Species varied considerably, however, in their responses to both environment and richness levels. Mechanistic models and experiments are now needed to understand and predict joint evolutionary dynamics of species in diverse communities.